Plasma Proteomic Markers of Iron and Risk of Diabetes in a Cohort of African American and White American Current and Former Smokers - Conway RB; Pratte KA; Bowler RP; Young KA; Kinney GL; Austin E; Li Y; McClain D; Hokanson J; Crapo JD (Diabetes, Metabolic Syndrome and Obesity)
Rebecca Baqiyyah Conway,1 Katherine A Pratte,2 Russell Paul Bowler,3 Kendra A Young,1 Gregory l Kinney,1 Erin Austin,4 Yisha Li,1 Donald McClain,5 John Hokanson,1 James D Crapo6 1Department of Epidemiology, University of Colorado, Anschutz Medical Campus, Aurora, CO, 80045, USA; 2Division of Biostatistics and Bioinformatics, National Jewish Health, Denver, CO, 80206, USA; 3Department of Genomic Sciences, Cleveland Clinic Foundation, Cleveland, OH, 44195, USA; 4Department of Mathematical and Statistical Sciences, Denver, University of Colorado, Denver, CO, 80204, USA; 5Section of Endocrinology and Metabolism, Wake Forest School of Medicine, Winston-Salem, NC, USA; 6Department of Medicine, National Jewish Health, Denver, CO, 80206, USACorrespondence: Rebecca Baqiyyah Conway, Department of Epidemiology, University of Colorado, Anschutz Medical Campus, 13001 East 17th Place, Mail Stop B119, Aurora, CO, 80045, USA, Email rebecca.conway@cuanschutz.eduBackground: Little information is available on iron with diabetes risk among African Americans, a population where both anemia and elevated ferritin are common. We tested whether plasma proteomic measurements of ferritin and transferrin were associated with increased diabetes risk in a cohort of current and former African American (NHB) and Non-Hispanic White (NHW) smokers.Methods: NHB and NHW participants from the COPDGene study who were free of diabetes (n = 4693) at baseline were followed for incident diabetes. The SomaScan was used to determine the relative amounts of natural log-transformed ferritin, transferrin, and hepcidin.Findings: During an average of 5.6 years of follow-up, diabetes incidence was 7.9%. Ferritin at follow-up was higher in NHB than NHW participants (p = < 0.0001). Ferritin at follow-up was associated with increased diabetes risk (OR = 1.36, 95% CI = 1.08– 1.70), while transferrin was associated with decreased risk (OR = 0.25, 95% CI = 0.08– 0.77) controlling for age, sex, BMI, smoking pack-years, hepcidin, CRP, and Il-6. Race-specifically, increased risk associated with higher ferritin levels among NHB (OR = 1.56, 95% CI = 1.13– 2.16) but not NHW (OR = 1.22, 95% CI = 0.89– 1.68) participants. Sex-specifically, ferritin’s relationship was similar among NHB men and women and NHW women (ORs ranging from 1.41– 1.59); but not NHW men (OR = 0.98, 95% CI = 0.64– 1.49). Similarly, transferrin ORs non-significantly ranged from 0.19– 0.30 for NHB men and women and NHW women, but was significant for NHW men (OR = 0.07, 95% CI = 0.01– 0.63).Interpretation: Higher body iron stores is associated with increased diabetes risk among both NHB and NHW people. Unsuspected elevated iron stores may increase diabetes risk in NHB patients and should be monitored.Keywords: diabetes, iron, ferritin, transferrin, African Americans